2011
DOI: 10.1007/s10562-011-0567-5
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Active Pd on Ni–B Bimetallic Catalyst for Liquid-Phase Hydrodechlorination of 4-Chlorophenol Under Mild Conditions

Abstract: A Pd on Ni-B (Pd/Ni-B) bimetallic catalyst was prepared and tested in the hydrodechlorination (HDC) of 4-chlorophenol (4-CP). The catalysts were synthesized by replacement method and treated at different temperatures (298-673 K). The results showed that the one treated at 473 K could achieve complete dechlorination of 200 ppm 4-CP under the pH = 8 within 30 min and keep the high activity in the first four recycles. The introducing of Pd greatly promoted the catalytic HDC efficiency of Ni-B, and the high disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…It can not only be operated under mild conditions, but also deal with chlorinated compounds within a wide range of concentrations. Transitional and noble metals (Ni, Rh, Ru, Pt, Pd) have been widely applied as active species of catalysts for liquid phase HDC [14][15][16]. Among such metals, Pd has been commonly researched because of its high dechlorination efficiencies [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can not only be operated under mild conditions, but also deal with chlorinated compounds within a wide range of concentrations. Transitional and noble metals (Ni, Rh, Ru, Pt, Pd) have been widely applied as active species of catalysts for liquid phase HDC [14][15][16]. Among such metals, Pd has been commonly researched because of its high dechlorination efficiencies [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Transitional and noble metals (Ni, Rh, Ru, Pt, Pd) have been widely applied as active species of catalysts for liquid phase HDC [14][15][16]. Among such metals, Pd has been commonly researched because of its high dechlorination efficiencies [13][14][15]. In the past few years, carriers of catalysts such as activated carbon (AC) [14], alumina (Al 2 O 3 ) [12], mesoporous silica-carbon (MSC) [13] and polymers [17] have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent the poisoning of the catalysts, hydrochloric acid (HCl) produced during the HDC process was neutralized by the bases added to the reaction system. 34 Therefore, NaOH was first used as a neutralizer to test different solvents ( In order to investigated the application of the Pd/Fe 3 O 4 @hTiO 2 nanocatalyst for HDC of chlorophenols, we also studied the HDC of 2-CP, 3-CP and 2,4-dichlorophenol (2,4-DCP) catalyzed by the Pd/Fe 3 O 4 @hTiO 2 nanocatalyst and the corresponding results were listed in Table 2. The values listed in Table 2 revealed that 3-CP and 2-CP were also almost completely transformed into phenol within 2 h. Except, the low yields of phenol obtained from 2,4-DCP.…”
Section: Catalytic Activity For Hdc Of 4-cpmentioning
confidence: 99%
“…Chlorophenols (CPs), existing widely in polluted groundwater and the wastewater effluents of industry [1,2], have been listed as priority pollutants in many countries because of their high toxicity, adverse environmental impacts and poor biodegradability [3][4][5]. For the safe disposal of these highly toxic chlorinated organic pollutants, many detoxification techniques such as biodegradation [6], photochemical degradation [5], advanced oxidation [7,8] and catalytic hydrodechlorination [9,10] have been proposed.…”
Section: Introductionmentioning
confidence: 99%